2000
DOI: 10.1590/s0301-80592000000100018
|View full text |Cite
|
Sign up to set email alerts
|

Identificação através de PCR dos genes CryI de cepas de Bacillus thuringiensis Berliner eficientes contra a lagarta do cartucho, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae)

Abstract: An. Soc. Entomol. Brasil 29(1): 147-153 (2000) PCR Identification of Cry I Genes in Bacillus thuringiensis Strains that are Efficient Against Fall Armyworm Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)ABSTRACT -Fall armyworm, Spodoptera frugiperda (J. E. Smith), is the most important maize insect pest in Brazil and its damage can reduce yield up to 34%. The objective of this work was to utilize the PCR technique to Identify Bacillus thuringiensis (B.t) strains that control S. frugiperda in mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
8
0
5
Order By: Relevance
“…Moreover, previous studies had shown clear advantages for this specific composition of Cry proteins (including Cry1E) on the toxicity to S. frugiperda under tropical conditions [26]. Therefore, on the basis of preliminary studies [26,44] and on the laboratory and field bioassays of this work, the Btt 01 strain showed a great potential for use in biocontrol applications, mostly in the form of biopesticides based on parasporal inclusions of proteinaceous (hence thermolabile) nature.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, previous studies had shown clear advantages for this specific composition of Cry proteins (including Cry1E) on the toxicity to S. frugiperda under tropical conditions [26]. Therefore, on the basis of preliminary studies [26,44] and on the laboratory and field bioassays of this work, the Btt 01 strain showed a great potential for use in biocontrol applications, mostly in the form of biopesticides based on parasporal inclusions of proteinaceous (hence thermolabile) nature.…”
Section: Discussionmentioning
confidence: 81%
“…Because of this health and environmental threat, the World Health Organization has prohibited the use of Bt strains producing this toxin in bioinsecticide formulations [50], though some countries still use β-exotoxin products in specific control programs of flies that are resistant to other insecticides [51]. Considering the positive results of this study in relation to the potential use of this tropical strain in biocontrol strategies, based on its δ-endotoxins composition [25,26,44] and action in the field, it is here postulated that the assessment of Bt collections also for the presence of β-exotoxins appears to be a necessary routine in research labs and companies producing Bt -based bioinsecticides. One can, for example, include tests with SN-heated aliquots [28,31,32] to assess for entomotoxicity and thermostability; once the latter is detected, further inactivation-based characterization such as those employed here can be used.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates containing cyt genes identified in this study showed different levels of toxicity against S. frugiperda (Valicente et al, 2000;Valicente & Barreto, 2003;Valicente & Fonseca, 2004;Valicente et al, 2010). Two isolates caused 100% mortality (isolates 1646JAB and 1656JAB) and one caused 79% of larval mortality (strain 1168C).…”
Section: Screening Of Cyt Genes In Bt Collectionmentioning
confidence: 77%
“…Studies performed 20 with mosquitoes bred in insectariums in Mexico and 24 Brazil showed the presence of Gram-negative bacteria in their intestines. Some bacteria are being used as biological 13,49,5,50 pest control of adult insects and larvae in plantations , while others are being tested as an alternative to controlling transmission by various insects . In a 2007 study , more than 20 bacteria species were isolated from horseflies and preserved, including those belonging to the Staphylococcus, Streptococcus and Serratia genera.…”
Section: Introductionmentioning
confidence: 99%